2021
DOI: 10.33989/2226-4078.2021.2.239959
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiarities of Professional Self-Actualization of Students-Psychologists Who Experiencing the Crisis of Professional Readiness

Abstract: The article is devoted to the problem of features of professional self-actualization of students-psychologists living in crisis of professional readiness. The definition of the term self-actualization and professional self-actualization among the works of domestic, Russian and foreign scientists is considered. In particular, professional self-actualization is defined as a complex multilevel phenomenon, a process of directed activity aimed at progress in one's own professional development, which is conditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been suggested that the higher the level of professional self-actualization, the lower the intensity of the professional readiness crisis (Stutoliarchuk, 2014). To confirm this hypothesis, it is important to understand the factors on which professional self-actualization depends, its determined the subject of this study (Gutyria & Kononova, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that the higher the level of professional self-actualization, the lower the intensity of the professional readiness crisis (Stutoliarchuk, 2014). To confirm this hypothesis, it is important to understand the factors on which professional self-actualization depends, its determined the subject of this study (Gutyria & Kononova, 2021).…”
Section: Introductionmentioning
confidence: 97%